Couple's relative labor supply in intermarriage - Olga Nottmeyer (Institute for the Study of Labor (IZA), 2011)
In this paper the hypothesis that partnerships between immigrants and natives are less specialized in the sense that spouses provide similar working hours per weekday than those between immigrants is tested. The empirical analysis relies on panel data using a two-limit random effects tobit framework to identify determinants of a gender-neutral specialization index. Results indicate that for immigrants intermarriage is indeed related to less specialization as is better education and smaller diversion in education between spouses. In contrast, children living in the household, as well as being Muslim or Islamic, lead to greater specialization. Intermarried immigrants specialize less presumably due to smaller comparative advantages resulting from positive assortative mating by education and different bargaining positions within the household. Natives, on the other hand, show different patterns: for them the likelihood to specialize increases with intermarriage. This might also results from differences in bargaining strength or be due to adaptation to immigrants' expected behavior.
urn:nbn:de:101:1-201104133891
Keywords: J1; J12; 330; migration; integration; intermarriage; specialization; division of labor; Ehe; Migranten; Bevölkerung; Arbeitsangebot; Familienökonomik; Schätzung; Deutschland